Analisis Pemikiran Imam Syafi’i dan Imam Ibnu Hazm terhadap Cacat sebagai Alasan Perceraian Perspektif Maslahah Mursalah - Amelia Rahman; Arsal Arsal (Lembaga Yasin AlSys, 2026)
Although defects as grounds for divorce in Islamic law have received attention in various previous studies, research that specifically compares the thought of Imam Syafi’i and Imam Ibnu Hazm from the perspective of maslahah mursalah remains limited. This study aims to analyze the views of Imam Syafi’i and Imam Ibnu Hazm regarding defects as grounds for divorce and their relevance from the perspective of maslahah mursalah. This study used a qualitative approach with a library research design. The data sources consisted of primary sources, namely al-Umm by Imam Syafi’i and al-Muhalla by Imam Ibnu Hazm, as well as secondary sources in the form of books, journals, scientific articles, and other documents relevant to the research theme. Data were collected through documentation and literature study techniques and were then analyzed using inductive, deductive, and comparative methods. The results showed that Imam Syafi’i permitted certain defects to be used as grounds for divorce if such defects obstructed the objectives of marriage and caused harm to the spouse. Conversely, Imam Ibnu Hazm argued that defects could not be used as grounds for divorce because there was no scriptural text that explicitly allowed the annulment of marriage due to defects. This difference in views was influenced by the legal istinbāṭ methods used by the two figures; Imam Syafi’i referred to the Qur’an, Sunnah, ijma’, and qiyas, whereas Imam Ibnu Hazm was more oriented toward a textualist approach to scriptural texts. The conclusion of this study affirms the importance of considering public benefit in understanding the dynamics of contemporary Islamic family law, particularly in relation to divorce due to defects. These findings provide a theoretical contribution to the development of Islamic family law studies by clarifying the relationship between maslahah mursalah, maqasid al-syari’ah, and divorce due to defects.